Dignity of patients with multiple sclerosis: a qualitative descriptive study - Podolinská, Lucia; Čáp, Juraj (Central European Journal of Nursing and Midwifery, 2021)
Aim: The aim of the study was to identify the impact of multiple sclerosis (MS) on the dignity of patients. Design: A qualitative descriptive design. Methods: Semi-structured interviews with eight participants were used to collect empirical data. The mean age of participants was 50 years. On average, participants were 21.9 years after diagnosis. A thematic analysis was used to analyze the data. Results: 21 sub-themes emerged from thematic analysis, which were grouped into four interconnected themes: Identity change and coping; Quality of social interaction and relationships; Living with the symptoms of the disease; and Violation of a fully-fledged life. The results indicate that MS can undermine patients' dignity and identity. Living with the symptoms of the disease impairs their quality of social interaction and relationships, their lives become restricted, and they must cope with a changed identity. Acceptance of the illness, a spirit of resistance to its effects, and a sense that they can still be of use help patients maintain dignity. Conclusion: Knowing and understanding the themes that patients with MS associate with dignity, can significantly help healthcare professionals to maintain and promote it in nursing care.
Keywords: uznání; rozhovory jako téma; Social Support; kvalita života; lidé; Multiple Sclerosis; Interviews as Topic; roztroušená skleróza; Respect; sociální opora; Quality of Life; Humans